Treatment of low-strength ammonia wastewater by single-stage partial nitritation and anammox using upflow dual-bed gel-carrier reactor (UDGR) - Jo, Yeadam; Cho, Kyungjin; Choi, Hyungmin; Lee, Changsoo (Elsevier BV, 2020)
This study investigated the single-stage partial nitritation and anammox (S-PNA) treatment of low-strength ammonia wastewater (<= 140 mg NH4+-N/L). Upflow dual-bed gel-carrier reactor (UDGR) with polyvinyl al- cohol cryogel biocarriers, developed in this study, was employed for the anammox biomass enrichment from conventional activated sludge and subsequent S-PNA experiments. Anammox biomass was successfully enriched from conventional activated sludge. The enriched anammox carriers were inoculated together with gel carriers containing nitrifying sludge into the S-PNA reactors. S-PNA activity developed rapidly, and the nitrogen removal efficiency and rate reached up to 90.1% (with complete ammonia removal) and 0.15 kg N/m(3).d, respectively, under low nitrogen loading conditions (0.10-0.17 kg N/m(3).d). The microbial community structure changed significantly while adapting to anammox and S-PNA conditions. Anammox was likely driven solely by a Candidates Jettenia population accounting for <= 49.4% of bacterial 16S rRNA genes. The results demonstrate that the UDGR-based S-PNA is suitable for treating low-strength wastewater.